COIN : a customisable, incentive driven video on demand framework for low-cost IPTV services - Musvibe, Ray (Rhodes University, Faculty of Science, Department of Computer Science, 2012)
There has been a significant rise in the provision of television and video services over IP (IPTV) in recent years. Increasing network capacity and falling bandwidth costs have made it both technically and economically feasible for service providers to deliver IPTV services. Several telecommunications (telco) operators worldwide are rolling out IPTV solutions and view IPTV as a major service differentiator and alternative revenue source. The main challenge that IPTV providers currently face, however, is the increasingly congested television service provider market, which also includes Internet Television. IPTV solutions therefore need strong service differentiators to succeed. IPTV solutions can doubtlessly sell much faster if they are more affordable or low-cost. Advertising has already been used in many service sectors to help lower service costs, including traditional broadcast television. This thesis therefore explores the role that advertising can play in helping to lower the cost of IPTV services and to incentivise IPTV billing. Another approach that IPTV providers can use to help sell their product is by addressing the growing need for control by today's multimedia users. This thesis will therefore explore the varied approaches that can be used to achieve viewer focused IPTV implementations. To further lower the cost of IPTV services, telcos can also turn to low-cost, open source platforms for service delivery. The adoption of low-cost infrastructure by telcos can lead to reduced Capital Expenditure (CAPEX), which in turn can lead to lower service fees, and ultimately to higher subscriptions and revenue. Therefore, in this thesis, the author proposes a CustOmisable, INcentive (COIN) driven Video on Demand (VoD) framework to be developed and deployed using the Mobicents Communication Platform, an open source service creation and execution platform. The COIN framework aims to provide a viewer focused, economically competitive service that combines the potential cost savings of using free and open source software (FOSS), with an innovative, incentive-driven billing approach. This project will also aim to evaluate whether the Mobicents Platform is a suitable service creation and execution platform for the proposed framework. Additionally, the proposed implementation aims to be interoperable with other IPTV implementations, hence shall follow current IPTV standardisation architectures and trends. The service testbed and its implementation are described in detail and only free and open source software is used; this is to enable its easy duplication and extension for future research.,TeX output 2012.03.02:1241,Adobe Acrobat 9.2 Paper Capture Plug-in
Keywords: Internet television; Digital television; Television broadcasting -- Technological innovations; Multicasting (Computer networks); Video dial tone; Open source software; Telecommunication; Capital investments